Comparative Study of Internal Fixation of the Ulna and Distal Ulna Resection in Patients Older Than 70 Years With Distal Radius and Distal Metaphyseal Ulna Fractures. (July 2019) - Boretto, Jorge G.; Zaidenberg, Ezequiel E.; Gallucci, Gerardo L.; Sarme, Alejandro; De Carli, Pablo
Background: Acute management of fractures of the distal ulna that are associated with fractures of the distal radius remains difficult, particularly in the elderly.Methods: In this study, we investigated whether internal fixation of the distal ulna is associated with a higher rate of complications than resection of the distal ulna in patients older than 70 years. Twenty-four consecutive patients were included in this study, 12 of whom had undergone open reduction and internal fixation (ORIF) of the distal ulna, and 12 who had undergone distal ulna resection. Patients were retrospectively assessed for range of motion, grip strength, pain, and radiographic appearance. The functional outcome was evaluated by the Mayo Wrist Score. Complications were classified according to the Classification of Surgical Complications.Results: There were no differences in patient demographics between the 2 groups, except patient age. Clinical evaluation showed no difference at follow-up; however, there were significantly more complications associated with ORIF compared with resection.Conclusions: The results from our study show that women older than 70 years with fracture of the distal radius and distal ulna have a higher rate of complications if ORIF of the distal ulna is performed. Patients should be warned, by surgeons, of this in cases where ORIF of the distal ulna is suggested.